Aluminum alloy extrusion material and its manufacturing method

JP7634408B2Active Publication Date: 2025-02-21UACJ CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021060200
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-02-21
Estimated Expiration
2041-03-31

AI Technical Summary

Benefits of technology

【0011】 上記アルミニウム合金押出材は、上記特定の化学成分組成を有し、式1及び式2を具備するようにMgおよびSiの含有量を制御し、かつ、Mn含有量の範囲の適正化により繊維状組織を得ることによって、曲げ性(=耐圧壊性)を向上させている。これにより、例えば自動車等の構造部材に適した押出材を得ることが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634408000003
    Figure 0007634408000003
  • Figure 0007634408000004
    Figure 0007634408000004
  • Figure 0007634408000005
    Figure 0007634408000005
Patent Text Reader

Abstract

To provide a 6,000 series aluminum alloy extruded material that is a raw material of a structural member and has improved strength and collapse resistance compared with conventional ones, and a manufacturing method of the 6,000 series aluminum alloy extruded material.SOLUTION: An aluminum alloy extruded material is provided, containing Si: 0.4-1.3% (mass%, same hereinafter), Mg: 0.3-0.9%, Mn: 0.4-0.6%, Cu: less than 0.05%, and the balance of Al and inevitable impurities, wherein the Si content and the Mg content satisfy following expressions (1) and (2), the material has a fibrous internal structure, and wherein a 0.2% proof stress (MPa) and a bending angle (degree) in a VDA bending test satisfy the following expression (3). ([Mg%]-0.15)×([Si%]-0.25)≥0.113 (expression 1), ([Mg%]-0.45)×([Si%]-0.63)≤0.120 (expression 2), [bending angle]≥-[0.2% proof stress]+365 (expression 3).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy extrusion material that is used for structural members of automobiles and the like and has excellent strength and bendability, and a method for producing the same. [Background technology]

[0002] In recent years, social demands for weight reduction of automobile bodies have been increasing due to considerations of the global environment, etc. In order to meet such demands, aluminum alloy materials have been used in place of steel materials such as steel plates in automobile body parts such as panels (outer panels and inner panels such as hoods, doors, and roofs) and reinforcing materials such as bumper reinforcements and door beams.

[0003] In order to further reduce the weight of automobile bodies, it is necessary to expand the application of aluminum alloy materials to automobile structural members such as side members and other members, frames, pillars, etc., which contribute particularly to weight reduction among automobile parts. However, compared to the above-mentioned automobile panel materials, these automobile structural members require further strengthening of the material plate and the addition of new properties such as crushability (crush resistance, crush characteristics) that will lead to shock absorption during a vehicle collision and protection of passengers.

[0004] Due to the recent increase (tightening) of automobile collision safety standards, in Europe and other regions, automobile structural components such as the frames and pillars are required to satisfy the crushing characteristics (crushing resistance and shock absorption) in the event of an automobile collision, which are evaluated by the "VDA238-100 Plate bending test for metallic materials (hereinafter referred to as the VDA bending test)" standardized by the Association of the German Automotive Industry (VDA).

[0005] To date, 6000 series alloys that have been evaluated for crush resistance by VDA bending tests include, for example, the plate material described in Patent Document 1. The plate material in Patent Document 1 satisfies certain required characteristics as a structural member, with a bend angle of 90° or more and a 0.2% yield strength of 250 MPa or more in the VDA bending test, but in recent years, there has been a demand for even higher strength and improved crush resistance in structural members for automobiles and the like.

[0006] Furthermore, structural components such as side sills have a complex cross-sectional shape and cannot be manufactured by press molding using plate material. For this reason, extrusion materials that can produce long products with complex cross-sectional shapes are suitable, but there are few extrusion materials that satisfy the crushing properties in accordance with the VDA standard. For example, Patent Document 2 proposes a 6000 series alloy extrusion material for use in automobile frame materials, but it is characterized by the absence of cracks under bending processing conditions and does not mention the crushing resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-125240 A [Patent Document 2] Patent Application No. 5-171328 Summary of the Invention [Problem to be solved by the invention]

[0008] Extrusion materials that satisfy the requirements for further increased strength and crush resistance are required for structural members such as side sills.

[0009] The present invention has been made in view of the above background, and aims to provide a 6000 series aluminum alloy extrusion material, which can be used as a raw material for structural components having improved strength and crush resistance compared to conventional materials, and a manufacturing method thereof. [Means for solving the problem]

[0010] One aspect of the present invention is a method for producing a Si:0.6 ~1.3% (mass%, same below), Mg: 0.3~ 0.6% , Mn: 0.4 to 0.6%, Cu: less than 0.05%, the balance being Al and unavoidable impurities, and further having a chemical composition in which the Si content and the Mg content satisfy the following formula 1 and formula 2, The internal tissue is made of fibrous tissue, The 0.2% yield strength is 240 MPa or more, The 0.2% yield strength (MPa) and the bending angle (degrees) in the VDA bending test are in an aluminum alloy extrusion material that satisfy the following formula 3. ([Mg%]-0.15)×([Si%]-0.25)≧0.113 (Equation 1) ([Mg%]-0.45)×([Si%]-0.63)≦0.120 (Formula 2) [Bending angle] ≧ - [0.2% yield strength] + 365 (Formula 3) Effect of the Invention

[0011] The aluminum alloy extrusion material has the specific chemical composition described above, and the Mg and Si contents are controlled so as to satisfy formula 1 and formula 2, and a fibrous structure is obtained by optimizing the range of the Mn content, thereby improving the bendability (= crush resistance). This makes it possible to obtain an extrusion material suitable for structural members of automobiles, for example. [Brief description of the drawings]

[0012] [Figure 1] 4 is an optical microscope photograph of the metal structure of Example 2. [Diagram 2] Metal structure photograph of Comparative Example 12. [Diagram 3] 4 is an optical microscope photograph of a cross section showing the corrosion test results of Example 22. [Figure 4] 4 is an optical microscope photograph of a cross section showing the corrosion test results of Example 23. [Diagram 5] 4 is an optical microscope photograph of a cross section showing the corrosion test results of Comparative Example 24. [Figure 6] 4 is an optical microscope photograph of a cross section showing the corrosion test results of Comparative Example 25. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] First, the chemical composition will be described.

[0014] Si: 0.4-1.3%; Si (silicon) coexists with Mg to form Mg2Si, which is effective in improving strength. If the Si content is less than 0.4%, this effect cannot be obtained, and if it exceeds 1.3%, grain boundary precipitation of Si increases, and toughness and extrudability decrease. Therefore, the Si content is preferably in the range of 0.4 to 1.3%, preferably in the range of 0.6 to 1.3%, and more preferably in the range of 0.7 to 1.3%.

[0015] Mg: 0.3-0.9%; Magnesium (Mg) is effective in improving strength together with silicon. If the Mg content is too low, the effect of precipitation strengthening is not sufficiently obtained, and if the Mg content is too high, the deformation resistance during extrusion increases, resulting in poor extrudability. Therefore, the Mg content should be in the range of 0.3 to 0.9%, preferably in the range of 0.3 to 0.7%, and more preferably in the range of 0.3 to 0.6%.

[0016] Mn: 0.4-0.6%; Mn (manganese) crystallizes as an AlMnSi phase, and Mn that does not crystallize precipitates and has the effect of suppressing recrystallization during extrusion. This effect allows the structure after hot extrusion to be fibrous, and this makes it possible to achieve both high strength and improved bendability. If the Mn content is too low, the effect of suppressing recrystallization cannot be obtained, the recrystallized structure becomes coarse, and strength decreases, and since a fibrous structure cannot be obtained, bendability decreases. On the other hand, if the Mn content is too high, the hardenability decreases significantly, and the effect of improving strength cannot be obtained. Therefore, the Mn content is set to a range of 0.4 to 0.6%.

[0017] Cu: Less than 0.05% (excluding 0%) Although Cu (copper) has the effect of improving strength through solid solution strengthening, it is regulated to less than 0.05% because there is a risk of reducing corrosion resistance. Cu has a higher natural potential than aluminum, and promotes localized corrosion of aluminum. Note that Cu can be contained as an impurity, so it is difficult to reduce it to 0%.

[0018] Other elements; Other elements such as Ti, B, Fe, Zn, and V are unavoidable impurities, and the inclusion of each is permitted within the ranges stipulated by JIS standards for 6000 series alloys. For example, the following are permitted as unavoidable impurities: Ti up to 0.10%, B up to 0.10%, Fe up to 0.15%, Zn up to 0.10%, and V up to 0.10%.

[0019] Mg,Si range; Mg and Si must satisfy the following formulas 1 and 2. These formulas stipulate Mg and Si in 6000 series aluminum alloys to keep the strength within a certain range. If formula 1 is not satisfied, the strength is low and the alloy is not suitable for use as a structural member. If formula 2 is not satisfied, the strength is too high and the bendability is poor. Therefore, Mg and Si must be within the above-mentioned component range and must satisfy formulas 1 and 2. ([Mg%]-0.15)×([Si%]-0.25)≧ 0.113 (Formula 1) ([Mg%]-0.45)×([Si%]-0.63)≦0.120 (Formula 2)

[0020] <Manufacturing method> The following method can be used to manufacture the aluminum alloy extrusion material. That is, an ingot having the above-mentioned chemical composition is subjected to a homogenization treatment, The casting is subjected to hot extrusion to produce an extruded material; The extruded material is subjected to a quenching treatment and then a tempering treatment, The quenching treatment is performed by quenching the extruded material immediately after the hot extrusion process, or by reheating the extruded material cooled after the hot extrusion process to a solution treatment temperature and then quenching the same, The rapid cooling is a method for producing the aluminum alloy extrusion material, in which cooling is performed to at least 100° C. at a cooling rate of 10° C. / sec or more. The method will be described in more detail below.

[0021] (casting) In the melting and casting process, the molten aluminum alloy that has been melted and adjusted to have the above-mentioned chemical composition range is cast into a billet by appropriately selecting a normal melting and casting method such as semi-continuous casting (DC casting).

[0022] (Homogenization treatment) The homogenization treatment is intended to homogenize the structure, that is, to eliminate segregation within the crystal grains in the ingot structure, and to stabilize the fibrous structure after hot working by finely precipitating Al-Mn-Si compounds. The homogenization treatment is performed at a temperature range of 450 to 590 ° C for a holding time of 5 to 24 hours. If the heating temperature of the homogenization treatment is lower than 450 ° C, the segregation layer in the ingot is not homogenized, and further, the precipitation of Al-Mn-Si compounds becomes insufficient, resulting in a non-uniform structure after hot working. On the other hand, if the temperature is higher than 590 ° C, the ingot may melt locally, making it difficult to actually manufacture it.

[0023] (Hot extrusion processing) The ingot after homogenization is heated to a temperature of 450 to 550°C, and hot extrusion is performed while maintaining the temperature. If the ingot temperature is lower than 450°C, the extrusion load becomes high, making extrusion difficult. If the temperature is higher than 550°C, hot cracks may occur and the crystallized particles and precipitates may become coarse.

[0024] (Hardening treatment) After the extrusion, the extruded material is quenched. This quenching can be performed by either a method of quenching the extruded material immediately after the hot extrusion, or a method of reheating the extruded material cooled after the hot extrusion to the solution treatment temperature and then quenching it. In either case, the quenching must be performed at least to 100°C at a cooling rate of 10°C / sec or more.

[0025] The method of quenching the extruded material immediately after hot extrusion is applicable, for example, when the temperature of the extruded material immediately after hot extrusion is within a range of 500 to 560° C. Examples of the quenching method include water-cooling or forced air-cooling the extruded material at the outlet side of the extruder (press quenching).

[0026] In addition, regardless of the temperature of the extruded material after hot extrusion, it is possible to select a method in which the extruded material, which has been cooled by any method, is heated again to 500 to 560°C and then rapidly cooled. Examples of the cooling method include water cooling and forced air cooling.

[0027] In any of the above methods, water quenching is preferably used for rapid cooling. This ensures that the cooling rate for cooling to at least 100° C. is 10° C. / sec or more. If the cooling rate is less than 10° C. / sec, precipitation of solute elements will proceed during cooling, resulting in a decrease in the subsequent age hardening ability, making it difficult to ensure sufficient strength and crush resistance.

[0028] As described above, the temperature of the solution treatment is preferably 500 to 560°C. If the temperature is below 500°C, the re-dissolution of compounds such as Mg-Si compounds formed before the solution treatment becomes insufficient, the amount of dissolved Mg and the amount of dissolved Si decrease, and the strength decreases. Setting the temperature above 560°C is not preferable because fine precipitates containing transition metals may become coarse and a fibrous structure may not be obtained.

[0029] (Tempering treatment (artificial aging treatment)) Next, the extruded material after quenching is subjected to a tempering treatment (artificial aging treatment) in which the material is heated and held at 150 to 200°C for 5 to 24 hours. The temperature and holding time of the aging treatment are selected according to the desired strength, etc. If the aging temperature is low or the aging time is short, sufficient strength cannot be obtained. On the other hand, if the aging temperature is high or the aging time is long, the precipitates grow coarsely and the strength decreases.

[0030] (Microstructure) By employing the manufacturing method including the above heat treatment, the aluminum alloy extrusion material can have a fibrous structure with an average grain aspect ratio of 3.5 or more due to the effect of suppressing recrystallization by the addition of Mn. If the Mn content is outside the above-mentioned appropriate range, the metal structure of the obtained extrusion material will not be a fibrous structure but a recrystallized structure.

[0031] When measuring the aspect ratio of crystal grains to determine the fibrous structure, first, a sample with a cross section parallel to the extrusion direction of the aluminum alloy material (L-ST cross section) is used, and an image of the cross section is obtained by observing the cross section etched with hydrofluoric acid in a bright field or by observing the cross section anodized with polarized light.

[0032] Next, in the obtained image, the aspect ratio is measured for crystal grains in the range of 1 / 4t to 3 / 4t, where t is the thickness of the material. When the crystal grain length in the direction parallel to the extrusion direction is X and the crystal grain length in the direction perpendicular to the extrusion direction (thickness direction) is Y, X / Y is the aspect ratio. When measuring the aspect ratio, it is preferable to observe about three fields of view for one sample. In this case, it is preferable to analyze an image including an alloy material with a length of at least 500 μm as one field of view.

[0033] The aspect ratio can be measured using image analysis software or by directly measuring the image. When measuring the image directly, it is preferable to measure the aspect ratio of 10 or more crystal grains per field of view and use the average aspect ratio. For crystal grains within the field of view, those with a maximum crystal grain length Y in the thickness direction of 100 μm or less and an average aspect ratio of 3.5 or more are judged to have a fibrous structure, and those with an average aspect ratio of less than 3.5 are judged to have a recrystallized structure.

[0034] In addition, for some test materials, the crystal grains are observed as linear, making it difficult to measure the aspect ratio by image analysis. For such test materials, the fibrous structure is judged based on direct measurement by visual judgment using a crystal grain sample with an aspect ratio of 3.5.

[0035] To explain the visual judgment in detail, a rectangular parallelepiped with an aspect ratio of 3.5 is created and judged. If the crystal grain to be measured is longer than a rectangular parallelepiped with an aspect ratio of 3.5, it is judged to have an aspect ratio of 3.5 or more. Then, for the crystal grains in the field of view, if the maximum value of the crystal grain length Y in the thickness direction is 100 μm or less and there are 10 or more crystal grains with an aspect ratio of 3.5 or more per field of view, it is judged to have a fibrous structure.

[0036] (Strength and crush resistance) The 0.2% yield strength is used as a guideline for the strength required for structural components. The 0.2% yield strength is measured by conducting a tensile test on the extruded material after aging treatment. Additionally, the bending angle obtained by the VDA bending test is used as a guideline for crush resistance. A material is deemed to have passed the test if the 0.2% yield strength and bending angle in the VDA bending test satisfy the following relational expression 3. [Bending angle] ≧ - [0.2% yield strength] + 365 (Formula 3) EXAMPLES

[0037] Next, examples relating to the above-mentioned aluminum alloy extrusion material and the manufacturing method thereof will be described in detail, but the present invention is not limited to these.

[0038] [Experimental Example 1] In this example, aluminum alloy molten metal obtained by heating aluminum alloys having the chemical composition shown in Table 1 was formed into an ingot billet with a diameter of 90 mm, which was homogenized at 500 to 590°C and extruded at a billet heating temperature of 520°C and an extrusion speed of 6 m / min to obtain an extruded plate material (test material) with a thickness of 1.5 mm and a width of 70 mm. Next, quenching was performed at the quenching speed shown in Table 1, and artificial aging treatment was performed at 185°C for 6 hours.

[0039] (Microstructure observation) For the test material after aging treatment, a cross section parallel to the extrusion direction (L-ST cross section) was cut out, the cross section was mirror-polished, and etched by anodizing treatment, and then the cross section was observed with polarized light using an optical microscope. The aspect ratio was measured based on the observed image, and it was determined that an average aspect ratio of 3.5 or more was a fibrous structure, and an average aspect ratio of less than 3.5 was a recrystallized structure. For reference, an image of Example 2 is shown in FIG. 1 as an example of a fibrous structure, and an image of Comparative Example 12 is shown in FIG. 2 as an example of a recrystallized structure that does not fall under the category of a fibrous structure.

[0040] (Tensile test) From the test material after aging treatment, JIS Z 2241:2011 No. 5 test pieces were taken and tensile tests were carried out at room temperature. The tensile direction of the test pieces was parallel to the extrusion direction. The test method was JIS In accordance with Z 2241:2011, the gauge length was 50 mm, and the tensile speed was initially set to 2 mm / min, and after the 0.2% proof stress measurement, it was set to 20 mm / min.

[0041] (VDA bending test) The bending test to evaluate the impact absorption was carried out in accordance with the German Association of the Automotive Industry (VDA) standard "VDA238-100 Plate bending test for metallic materials." The bending angle was calculated from the stroke at the maximum load based on the formula described in the aforementioned standard.

[0042] A material was deemed to have passed the test if the 0.2% yield strength obtained from the above tensile test and the bending angle obtained from the VDA bending test satisfied the following formula 3, in other words, met the requirements for use as a structural member. [Bending angle] ≧ - [0.2% yield strength] + 365 (Formula 3)

[0043] The results of each test are shown in Table 1.

[0044] [Table 1]

[0045] In Examples 1 to 6, aluminum alloys whose chemical compositions are within the appropriate ranges shown in Table 1 are used, and quenching is performed at an appropriate quenching rate, so that the internal structure is a fibrous structure with an average aspect ratio of 3.5 or more, as shown in Figure 1. This makes it possible to obtain high strength and good bendability, and as shown in Table 2, the relationship between the 0.2% proof stress and the bending angle in the VDA bending test satisfies Formula 3.

[0046] In Comparative Examples 7 to 13, the contents of Mg, Si, and Cu are within the appropriate ranges, but since Mn is not added, a fibrous structure is not formed, and the recrystallized structure has an average aspect ratio of less than 3.5 as shown in Figure 2. The 0.2% proof stress is relatively high at 250 to 270 MPa, but the bending angle value is low due to the recrystallized structure, and formula 3 is not satisfied.

[0047] In Comparative Examples 14 to 17, the contents of Mg and Si are within the appropriate ranges, but the amount of Cu added is greater than the appropriate range, and the Mn content is less than the appropriate range. Because Cu is added, the 0.2% proof stress is 260 to 290 MPa, which is higher than that of Comparative Examples 7 to 13. However, because the amount of Mn added is small, the recrystallized structure has an average aspect ratio of less than 3.5, the bending angle is low, and formula 3 is not satisfied.

[0048] In Comparative Example 18, the contents of Mg, Si, and Cu are within the appropriate ranges, but a large amount of Mn is added. If the amount of Mn added is too much, the hardenability is significantly reduced, and the strength is low, with a 0.2% yield strength of 137 MPa, and formula 3 is not satisfied.

[0049] Comparative Examples 19 to 21 use aluminum alloys whose chemical compositions are within the appropriate range, but the quenching speed is slow. As a result, the 0.2% proof stress is low at 150 to 170 MPa, and formula 3 is not satisfied.

[0050] [Experimental Example 2] In this example, aluminum alloys (Examples 22 and 23 and Comparative Examples 24 and 25) having a plurality of chemical composition compositions shown in Table 2 were used, and the homogenization treatment and artificial aging treatment were performed under the conditions shown in Table 2, with the other conditions being the same as those of Experimental Example 1, to obtain extruded flat plate materials (test materials). In Examples 22 and 23, all of the main chemical components were within the suitable range, while in Comparative Examples 24 and 25, the Cu content exceeded 0.05%. In this example, in addition to the evaluation items in Experimental Example 1, the following corrosion test was performed to investigate the relationship between the Cu content and corrosion resistance.

[0051] (Corrosion test) The corrosion test was conducted to evaluate intergranular corrosion resistance. The evaluation test for intergranular corrosion resistance was conducted in accordance with ISO11846 Method B. The test materials were each test material plate after solution treatment and artificial aging treatment. After degreasing with acetone, they were immersed in a cleaning solution of 70% HNO3 and 48% HF added to pure water heated to 95°C for 1 minute, washed with 70% HNO3, rinsed with water, and dried at room temperature. An aqueous solution containing HCl and NaCl (containing 30 g / L NaCl and 10±1 mL / L of 36% concentrated hydrochloric acid) was prepared as the etching solution, and the material was etched at 25°C for 24 hours with a surface area of ​​1 cm. 2The test materials were immersed in 5 ml of corrosion solution per 100 ml. The corrosion products were then removed by immersion in 70% HNO3 and brushing with a plastic brush, followed by rinsing with water and drying at room temperature. Each cross section was then observed with an optical microscope. When the maximum corrosion depth from the surface was 250 μm or less, the test materials were judged to have excellent corrosion resistance and pass (○), and when the maximum corrosion depth exceeded 250 μm, the test materials were judged to have poor corrosion resistance and fail (×). The evaluation results are shown in Table 2 together with other evaluation items.

[0052] [Table 2]

[0053] 3 to 6 show optical microscope photographs of the cross sections in which the results of the corrosion tests were observed for all the examples.

[0054] As can be seen from Table 2, all the examples showed good results except for the corrosion test, but in the corrosion test, Examples 22 and 23 passed, while Comparative Examples 24 and 25 failed.

[0055] As shown in Figs. 3 and 4, in Example 22 with a Cu content of less than 0.01% and Example 23 with a Cu content of 0.03%, no corrosion occurred at all after the corrosion test, and the corrosion resistance was excellent.

[0056] On the other hand, as shown in Figs. 5 and 6, in Comparative Example 24 with a Cu content of 0.07% and Comparative Example 25 with a Cu content of 0.10%, after the corrosion test, corrosion occurred with a maximum corrosion depth from the surface exceeding 250 µm, resulting in low corrosion resistance.

[0057] It can be seen from the results of Experimental Example 2 that it is very important to limit the Cu content to 0.05% or less in order to improve corrosion resistance.

Claims

1. The alloy has a chemical composition containing Si: 0.6 to 1.3% (mass%, the same applies below), Mg: 0.3 to 0.6%, Mn: 0.4 to 0.6%, Cu: less than 0.05%, and the balance being Al and unavoidable impurities, and further the Si content and the Mg content satisfy the following formula 1 and formula 2, The internal tissue is made of fibrous tissue, The 0.2% yield strength is 240 MPa or more, An aluminum alloy extrusion material in which the 0.2% proof stress (MPa) and the bending angle (degrees) in a VDA bending test satisfy the following formula 3. ([Mg%]-0.15)×([Si%]-0.25)≧0.113 (Formula 1) ([Mg%]-0.45)×([Si%]-0.63)≦0.120 (Formula 2) [Bending angle] ≧-[0.2% yield strength] + 365 (Equation 3)

2. The ingot having the above chemical composition is subjected to homogenization treatment, The casting is subjected to hot extrusion to produce an extruded material; The extruded material is subjected to a quenching treatment and then a tempering treatment, The quenching treatment is performed by quenching the extruded material immediately after the hot extrusion process, or by reheating the extruded material cooled after the hot extrusion process to a solution treatment temperature and then quenching the same, The method for producing an aluminum alloy extrusion material according to claim 1, wherein the rapid cooling is performed to at least 100°C at a cooling rate of 10°C / sec or more.

3. The method for producing an aluminum alloy extrusion material according to claim 2, wherein the rapid cooling is performed by water quenching.

Citation Information

Patent Citations

  • Thin hollow shape of aluminum alloy excellent in bendability and its production

    JP1993171328A

  • Self-coloring high-strength aluminum alloy material and its production

    JP1995126890A

  • Aluminum alloy extrusion material having excellent intergranular corrosion resistance, apparatus and thermostatic refrigerant expansion valve composing refrigeration cycle using the extrusion material

    JP2002206134A

  • Aluminum alloy structural member, manufacturing method thereof, and aluminum alloy sheet

    JP2017125240A